1976
DOI: 10.1037/0096-1523.2.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Visual masking during pursuit eye movements.

Abstract: In three experiments, targets and masking stimuli were briefly flashce while observers visually tracked a moving dot. Masking stimuli were more effective when they appeared to be in the same place as the target but stimulated different parts of the retina than when they stimulated the same parts of the retina but appeared displaced because of of an intervening pursuit eye movement. Visual masking during pursuit eye movements thus depended on the apparent position of the stimuli, not their retinal positions as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
(37 reference statements)
0
24
0
1
Order By: Relevance
“…A brief target is followed by the mask and then a saccade. Typically, backward masking is robust when the mask falls on the same retinotopic location as the target (Irwin, Brown, & Sun, 1988; Sun & Irwin, 1987), that is, even if a saccade occurs between the target and the mask, the masking is still seen at the retinotopic location, although there are also reports of spatiotopic masking (Deubel, Bridgeman, & Schneider, 1996; Irwin 1992; MacRae, Butler, & Popiel, 1987; White, 1976; but see Jonides, Irwin, & Yantis, 1983 for a cautionary note about monitor persistence). In a recent study, De Pisapia, Kaunitz, and Melcher (2010) showed what they refer to as target “unmasking” when a saccade intervened between a target and a mask shown at the same spatial location.…”
Section: Introductionmentioning
confidence: 99%
“…A brief target is followed by the mask and then a saccade. Typically, backward masking is robust when the mask falls on the same retinotopic location as the target (Irwin, Brown, & Sun, 1988; Sun & Irwin, 1987), that is, even if a saccade occurs between the target and the mask, the masking is still seen at the retinotopic location, although there are also reports of spatiotopic masking (Deubel, Bridgeman, & Schneider, 1996; Irwin 1992; MacRae, Butler, & Popiel, 1987; White, 1976; but see Jonides, Irwin, & Yantis, 1983 for a cautionary note about monitor persistence). In a recent study, De Pisapia, Kaunitz, and Melcher (2010) showed what they refer to as target “unmasking” when a saccade intervened between a target and a mask shown at the same spatial location.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lehmkuhle and Fox (1980) have recently shown that masking effects are much stronger when the target and induction figures are perceived to lie in the same plane. White (1976) had earlier shown that optimal masking effects occur when the target and induction figures are perceived as located in adjacent spatial positions rather than when they are retinally adjacent. Although retinal adjacency and perceived adjacency (in the frontal plane) are normally confounded, White teased them apart using a moving-eye technique analogous to that introduced by Rock and Ebenholtz (1962) to demonstrate that stroboscopic motion requires a change of perceived location, not a change of retinal location.…”
Section: Percept-percept Relationshipsmentioning
confidence: 99%
“…This forces us to emphasize that the Table 2 The Main Table for Selected Experimental Findings Subliminal effects of masked semantic information (e.g., Allport, 1977;Marcel & Patterson, 1978) -t Subliminal effects of masked geometric information (e.g., Kapustin, 1979;Gellatly, 1980) Masking increase with the increase in TS energy (e.g., Purcell et al, 1969Purcell et al, , 1975 The "halo" effect (e.g., Werner, 1935;Stoper & Mansfield, 1978) X Reappearance of TS after TS-MS fast recycling (Schiller & Smith, 1966) X Lack of spatial frequency specificity of metacontrast at the whole SOA range (Growney, 1978) X Nonretinotopic ("spatiotopic") nature of masking (White, 1976;Lehmkuhle & Fox, 1980) Asymmetric nonrandom recombinations of portions of TS and MS into single percept (Harcum & Nice, 1975) Dependence of MS perceptive quality on spatial distribution of the backwardmasked TS elements (Carlson & Mayzner, 1977) X Cohene and Bechtoldt effect (1974 -t The early EP components unchanged with masking (Bridgeman, 1980) Operational sufficiency index" term "nonspecific," which refers to certain physiological realities, does not necessarily mean something that is spatially undifferentiated. We can explain the asymmetric nature of traditional metacontrast masking, in which the disk-ring sequence leads to nonmonotonic backward masking but the ring-disk sequence does not, as follows.…”
Section: Data From Metacontrast Masking Studies In Llgbtof Tbeproposementioning
confidence: 99%